Analysis of traditional risk factors for ischemic heart disease in Nepalese females with anginal chest pain - Adhikari, Suman; Poudel, Rajendra; Thakuri, Surya Bahadur Hamal; Gautam, Suwash Chandra; Bidari, Prayas; Bastola, Basanta Kumar; Pradhan, Ashesh; Shakya, Aman; Ghimire, Sunita; Ghimire, Deen Dayalu; Devkota, Sandesh; Manandhar, Varsha (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Ischemic heart disease has emerged as one of the important causes of deaths in females in most of the countries. IHD is killing women more significantly in recent years. Females with anginal chest pain are often treated differently as compared to males at the time of presentation. In Nepalese female population, the burden and impact of traditional risk factors for IHD have been less studied.METHODS It was a single centre , hospital based, case control, descriptive study comprising of 155 female patients with angina in case arm and 155 otherwise healthy females in control arm. The study period was of one year duration. Cases and controls were matched in a 1:1 frequency matching manner with respect to age. Written consents were taken. Data were collected after complete history taking, physical examination, laboratory investigations. Subsequently statistical analysis was done. First bivariate analysis followed by multivariate analysis were done using latest version of SPSS in regards to comparison of risk factors between two groups.RESULTS The average age of cases was 60.50 ± 11.13 years and 60.37 ± 10.68 years for controls. The most prevalent risk factor of IHD in cases and control was HTN (53.3% vs 40%). The statistically significant risk factors for IHD that were found in females with angina were - Smoking (AOR=3.190, 95% CI:1.606, 6.334 and p=0.001), Diabetes (AOR=2.573, 95% CI: 1.346, 4.918 and p=0.004) , and Obesity/overweight (AOR=2.482, 95% CI: 1.475, 4.176 and p=0.001).CONCLUSION The important risk factors for IHD that are associated significantly with likelihood of having angina in Nepalese females are smoking, diabetes and overweight/obesity in our study.